Damage mitigation and retrofit of non-structural components on buildings subjected to blast loading - Holgado, David (2019)
Structures in chemical and petrochemical facilities are often located in areas that may be subjected to blast loading. Occupied buildings typically have non-structural components located along the interior of the exterior walls and roof such as windows, doors, wall mounted AC units, lights, furniture, storage racks, hanging equipment, and loose articles. Occupants of buildings subjected to accidental explosions may be injured from glass fragments and interior non-structural items becoming projectiles and impacting building occupants. As a pressure wave from a blast impacts the exterior of a building, the wall and roof components are rapidly accelerated inward. Equipment or contents mounted on or in contact with the exterior façade are also accelerated and may be dislodged and projected as debris. Items anchored to the ceiling structure can be thrown vertically from the initial forward deflection of the supporting member or break free from their supports and become falling debris hazards. Therefore, evaluation and mitigation of non-structural debris for buildings subjected to blast load is important to further mitigate the potential hazards to personnel occupying these buildings. This paper provides design retrofit recommendations based on accident investigation experience at chemical and refining facilities and engineered solutions for typical hazards commonly observed at these facilities.